Efforts To Empower The Turnover Rate In Order To Increase Employee Performance - Desy Puspita; Zahriatul Aini (Enrichment : Journal of Management, 2021)
Human resources are an asset for a company. It is said that assets, it is clear that human resources must be maintained as well as possible and even have to be improved in terms of quality. The performance of a company will increase if the quality of its human resources also increases. There are several factors that affect the company's performance, one of which is Turnover Intention. Turnover Intention is a process where human resources leave the organization and must be replaced. Turnover Intention is also a voluntary or involuntary withdrawal from the company. Actually, Turnover Intention is something that companies really avoid. Companies will spend a lot of money during the recruitment process. Turnover Intention is also influenced by several factors such as work involvement and work stress. Employees in a company will think about leaving the company if they feel they have never been involved in work and experience work stress. Several construction sectors companies in Banda Aceh City, during the last three (3) years experienced an increase in turnover rates. This is a concern for the company because the increasing turnover rate will reduce the company's performance. Observations made to construction sector companies in Banda Aceh found that employees experienced work stress and felt that they were rarely involved in the work process. This research later is to reduce the turnover rate so as to improve the company's performance. The purpose of this study is a) To reduce the number of Turnover Intention of the Company b) To improve the Company's Performance.